2019
DOI: 10.3390/microorganisms7110505
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Rhizosphere Fungal Communities to the Sewage Sludge Application into the Soil

Abstract: Due to the increasing sewage sludge production in the world and problems with its disposal, an application of sludge to the soil appears to be a suitable solution considering its fertilizer properties and ability to improve the soil physical conditions. On the other hand, the sludge may also contain undesirable and toxic substances. Since soil microorganisms are sensitive to environmental changes, they can be used as indicators of soil quality. In this study, we used sewage sludge (SS) from two municipal waste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 61 publications
(69 reference statements)
0
15
1
Order By: Relevance
“…In these experiments, we found that the total microbial biomass statistically increased with the addition of SS [22]. Likewise, the alpha diversity of fungal rhizosphere communities was significantly increased in sludge-added soils, and more varied fungal taxa were detected in the soil sample with SS when compared to the control treatment [23]. Enhanced biological parameters of the soil were also confirmed by Kołodziej et al [19] by measuring the soil enzymes as markers of biological fertility during the cultivation of sweet sorghum in an SS-amended soil.…”
Section: Evaluation Of Growth Parameters and Biomass Yield At The Endmentioning
confidence: 71%
See 1 more Smart Citation
“…In these experiments, we found that the total microbial biomass statistically increased with the addition of SS [22]. Likewise, the alpha diversity of fungal rhizosphere communities was significantly increased in sludge-added soils, and more varied fungal taxa were detected in the soil sample with SS when compared to the control treatment [23]. Enhanced biological parameters of the soil were also confirmed by Kołodziej et al [19] by measuring the soil enzymes as markers of biological fertility during the cultivation of sweet sorghum in an SS-amended soil.…”
Section: Evaluation Of Growth Parameters and Biomass Yield At The Endmentioning
confidence: 71%
“…In our previous papers, samples of municipal SS were evaluated for the responses of rhizosphere bacterial [22] and fungal [23] communities to the application of SS into the soil. The present work aimed to assess the effect of SS on the growth parameters and the biomass yield of giant reed plants.…”
Section: Introductionmentioning
confidence: 99%
“…Using biological approaches to determine the ecological effects of land application of municipal SS has been preferred widely for decades [ 4 , 28 ]. Alpha diversity [ 34 ] indicates the diversity that exists within a sample/location, and it is measured by the number of species or the richness of species but other diversity indices are often used, such as Shannon and Simpson [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The quantity and purity of DNA were measured spectrophotometrically with a NanoDrop-1000 Spectrophotometer (Thermo Fisher Scientific Inc., Waltham, MA, USA), and samples were diluted to the same final concentration (20 ng μL −1 ) and stored at −20°C. Molecular analysis of partial 18S rRNA gene using two conserved primer pairs NS1 with NS4 [ 26 ] and NS31 with AM1 [ 27 ] in terminal restriction fragment length polymorphism (T-RFLP) was performed according to our previous study [ 28 ]. The second primer pair is specific for AMF; however, it should be noted that it also amplifies DNA from Ascomycota and Basidiomycota to a limited extent [ 28 , 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation